Cardiac 18F-FDG Positron Emission Tomography: An Accurate Tool to Monitor In vivo Metabolic and Functional Alterations in Murine Myocardial Infarction - Fischer, Maximilian; Zacherl, Mathias J.; Weckbach, Ludwig; Paintmayer, Lisa; Weinberger, Tobias; Stark, Konstantin; Massberg, Steffen; Bartenstein, Peter; Lehner, Sebastian; Schulz, Christian; Todica, Andrei (Frontiers in Cardiovascular Medicine, 2021)
Cardiac monitoring after murine myocardial infarction, using serial non-invasive cardiac 18F-FDG positron emissions tomography (PET) represents a suitable and accurate tool for in vivo studies. Cardiac PET imaging enables tracking metabolic alterations, heart function parameters and provides correlations of the infarct size to histology. ECG-gated 18F-FDG PET scans using a dedicated small-animal PET scanner were performed in mice at baseline, 3, 14, and 30 days after myocardial infarct (MI) by permanent ligation of the left anterior descending (LAD) artery. The percentage of the injected dose per gram (%ID/g) in the heart, left ventricular metabolic volume (LVMV), myocardial viability defect, and left ventricular function parameters: end-diastolic volume (EDV), end-systolic volume (ESV), stroke volume (SV), and the ejection fraction (EF%) were estimated. PET assessment of the viability defect positively correlates with post-infarct histology at 3 and 30 days. Compared to their age-matched littermates, infarcted murine hearts show an immediate decrease in LVMV and an increase in %ID/g early after infarction, diminishing in the remodeling process. This study of serial cardiac PET scans provides insight for murine myocardial infarction models by novel infarct surrogate parameters. It depicts that serial PET imaging is a valid, accurate, and multimodal non-invasive assessment.